'Garuda shield' vs 'sharp knife': operationalising Indonesia's defence diplomacy. Issue 6 (7th October 2021) - Wenas Inkiriwang, Frega
Abstract: In the Post New Order period, there was a significant development in Indonesia. The issuance of the Law on TNI in 2004, has since guided how the Indonesian military operates in dealing with external and internal security threats and curbed its socio-political role, which is associated with the New Order regime. However, it has not explicitly touched upon the implementation of defence diplomacy, which has significantly increased within the last decade. Hence, the article aims to analyse the development of Indonesia's Defence Diplomacy in the Post New Order period, particularly in the context of joint exercises. This article attempts to answer two key questions: ' How has Indonesia developed its defence diplomacy as part of its overall diplomacy? ' and ' What factors account for different practices undertaken in Indonesia's defence diplomacy? ' The article qualitatively scrutinises the development of Indonesia's defence diplomacy activities of joint exercises by comparing two bilateral exercises with the major powers, the Garuda Shield and the Sharp Knife. In supporting the analysis, the article relies on the combination of interviews and observations performed during fieldwork from July 2018 to July 2019. The article is critical since it offers an alternative approach to studying Indonesia's defence diplomacy.